The Omphalos in the Floor Decor of the Churches of the Premongol Rus Period - Matveev, Vasilii N. (Actual Problems of Theory and History of Art, 2016)
The Omphalos is a specially marked place in central part of a temple. It originates from the sacred stone at Delphi, which is considered to be the “navel of the earth”. In Christian churches, it was situated in the center of the structure under the dome. On the territory of Kiev Rus, there were only 15 monuments where omphaloi were found. All the omphaloi of Rus could be divided into two groups depending on material and technology. The first one includes facings of the Tithe church and St. Sophia Cathedral in Kiev, the Church of Our Savior, Borisoglebskiy Cathedral and the Church of Annunciation in Chernigov. These omphaloi were laid with expensive prestigious materials: stones, smalt, and slate slabs inlaid with smalt. All these facings were found in churches located in the middle basin of the Dnieper River. The second group includes facings in the churches in Halich and Grodno regions: Spasskaya church and the Church of Annunciation in Halich, the rotunda in Oleshkov and Paraskeva church in Zvenigorod, Lower church in Grodno and the Church of Boris and Gleb in Nowogrudek. The composition in all of these monuments represents concentric circles inlaid entirely with glazed ceramic tiles with large gurative compositions in the center. These two variants show the development of two different traditions. Monuments of the rst group directly link to the tradition of Byzantine mosaics. Monuments of the second group are connected to it indirectly, probably through the Polish architectural tradition.